2011
DOI: 10.1007/s00464-011-1724-z
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and safety of total extraperitoneal inguinal hernia repair after previous lower abdominal surgery: a case–control study

Abstract: In experienced hands, TEP hernia repair for patients with previous lower abdominal surgery can be performed safely. In this study, the operative outcomes were comparable with those for patients who had no history of lower abdominal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 12 publications
1
13
1
Order By: Relevance
“…Shpits et al [14] reported that the peritoneal injury occurred in 22 % of patients undergoing primary repair and 41 % of patients undergoing treatment for recurrent hernia. In this study, peritoneal injuries were observed in 15 % of the patients in the control group, and 25 % of the patients in the PLAS group; these rates are comparable to previous reports (Table 4) [3,6]. We perform preperitoneal dissection gradually from the space under the intraumbilical skin incision, using standard laparoscopic instruments such as laparoscopic coagulation shears and blunt dissectors, since the blind balloon dilation of the preperitoneal space may dissect the preperitoneal space anterior to the inferior epigastric vessels, causing injury to the peritoneum, intraoperative bleeding, and a poor operative field, especially in patients with significant fibrotic adhesion after PLAS.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Shpits et al [14] reported that the peritoneal injury occurred in 22 % of patients undergoing primary repair and 41 % of patients undergoing treatment for recurrent hernia. In this study, peritoneal injuries were observed in 15 % of the patients in the control group, and 25 % of the patients in the PLAS group; these rates are comparable to previous reports (Table 4) [3,6]. We perform preperitoneal dissection gradually from the space under the intraumbilical skin incision, using standard laparoscopic instruments such as laparoscopic coagulation shears and blunt dissectors, since the blind balloon dilation of the preperitoneal space may dissect the preperitoneal space anterior to the inferior epigastric vessels, causing injury to the peritoneum, intraoperative bleeding, and a poor operative field, especially in patients with significant fibrotic adhesion after PLAS.…”
Section: Discussionsupporting
confidence: 94%
“…It is difficult to enter the preperitoneal space after previous surgery and to perform dissection during a TEP hernia repair due to adhesion. There have been few studies on the feasibility of TEP hernia repair after PLAS [2][3][4][5][6]. Furthermore, there have been no reports on the feasibility and safety of SILS-TEP in patients with PLAS [7,8].…”
Section: Introductionmentioning
confidence: 98%
“…Several other studies, however, have not found such history to be a deterrent to laparoscopic extraperitoneal surgery using a balloon dilator (11). Extraperitoneal space creation during hernia repair can be carried out safely in the presence of scars from previous lower abdominal surgery (12,13). Our patient had a paramedian scar from a prior exploratory laparotomy, which was not associated with the bladder tear.…”
Section: Discussionmentioning
confidence: 66%
“…). Of 11 full‐text articles assessed for eligibility, seven studies were included in the qualitative and quantitative data synthesis, involving a total of 1657 hernia repairs (PS 326, NS 1331). Studies excluded after full‐text review are summarized in Table S1 (supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…Previous lower abdominal surgery is often considered a relative contraindication to TEP repair, as access to the preperitoneal space may be challenging when scar tissue from previous interventions is encountered. Nonetheless, the feasibility and safety of TEP repair in patients with a history of lower abdominal surgery remains inconclusive. The aim of this study was to perform a meta‐analysis of trials comparing the feasibility and safety of TEP inguinal hernia repair in patients with (PS, previous surgery group) and without (NS, no previous surgery group) a history of lower abdominal surgery.…”
Section: Introductionmentioning
confidence: 99%